Characterization of the emerging multidrug‐resistant Salmonella enterica serotype Kentucky ST314 in China. (18th May 2021) - Wang, Shaojun; Liao, Xinmeng; Xiong, Zhiying; Lin, Qijie; Wen, Junping; Xu, Chenggang; Qu, Xiaoyun; Chen, Kaifeng; Zhang, Jianmin
Abstract: Salmonella enterica serotype Kentucky ( S . Kentucky) is an important Salmonella serotype with multiple sequence types (ST) with a worldwide incidence. We identified 8 STs from 180 strains of S . Kentucky, and ST314 emerged as the most commonly encountered ST. Drug susceptibility testing revealed that ST314 had multiple resistance properties, and 75.5% of the strains were resistant to three or more classes of antimicrobials. The rate of resistance to chloramphenicol, florfenicol, sulfafurazole and tetracycline were greater than 60%. The rates of ST314 resistance to quinolones were as follows: ciprofloxacin, 32.1%; nalidixic acid, 16%; and ofloxacin, 7.5%. Investigating the mechanism of quinolone resistance of ST314 revealed that mutations in the quinolone resistance‐determining regions were rare, and resistance mainly occurred due to the resistance genes carried by plasmids. Only 1.9% (2/106) of ST314 strains had mutations in the quinolone resistance‐determining regions (QRDR). The drug resistance genes of ST314 were primarily of plasmid‐mediated quinolone resistance (PMQR). The detection rate of Salmonella genomic island 1 (SGI1) in ST314 was 12.3%. XbaI ‐pulsed‐field gel electrophoresis revealed that S. enterica Kentucky ST314 was capable of cross‐regional and cross‐host transmission in China. We found ST314 to be the dominant S . Kentucky ST in China, and it carried multidrug resistance. This is the first report about the emergence of quinolone‐resistant S. enterica Kentucky ST314 in China, which is different from previous reports, and the findings of the present study suggest that the mechanism of quinolone resistance in these strains are plasmid‐mediated. Notably, plasmids carrying resistance genes may promote the rapid spread of ciprofloxacin resistance.